Efecto de soluciones nutritivas en 2 variedades de apio (Apium graveolens) sembrado en condiciones hidropónicas en la zona de Santo Domingo de los Tsáchilas. - Molina Mendieta, Javier Fernando (2017)
Taking into account the different soil problems either nutrient deficiency caused by excessive exploitation or the indiscriminate use of pesticides and contaminants in the soil, this research was motivated to measure the effect of nutritive solutions on 2 varieties of celery (Apium graveolens) planted under hydroponic conditions in the area of Santo Domingo de los Tsáchilas. To do this, seedlings were obtained in germination trays of two varieties, the transplant was carried out after 25 days and the plants were placed in the NFT hydroponic system. A completely randomized design (DCA) was used, with a factorial arrangement of 2 varieties and 4 treatments. To analyze the means, the Minimum Significant Difference (DMS) test was used. The treatments were: Nutrient solution A Potassium nitrate 50 ml. (12% N 12% P 17% K) + Super K 3 ml (12% N 8% P 16% K). Nutrient solution B Super K 3ml (12% N 8% P 16% K). Nutritional solution C Potassium nitrate 50 ml. (12% N 12% P 17% K). Nutrient solution D Yaramilá Complex 5454 g (12% N 11% P 18% K + 2.7 (MgO)). The Mambo celery variety achieved better results when measuring the variables, yielding 177.91 g, more than the Andean variety. Meanwhile the nutritive solution A, presented the best performance with a difference of 240.54 g, more than the other nutritive solutions. Key Words: Laminar flow technique of nutrients, nutritive solutions.